Faktor-Faktor yang Memengaruhi Partisipasi Petani Pada Program Upaya Khusus Jagung di Kabupaten Pandeglang - Rizki Triguna; Suharno Suharno; Andriyono Kilat Adhi (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2022)
The Special Efforts Program (UPSUS) is a government program to achieve sustainable food self-sufficiency, one of which is the commodity of corn. The success of the UPSUS program is inseparable from the participation of farmers. Some factors affect the level of farmer participation. This study aimed to analyze the factors that influence farmers' participation in the UPSUS program. The study was carried out from August to October 2019 in Pandeglang Regency. The research involved 94 respondents who were joined in the UPSUS Program on maize commodity. The data obtained were statistically analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis. The results showed that the ability of farmers and the opportunity factor had a positive and significant effect on the level of farmer participation. This implies that the higher farmers’ ability and the number of opportunities obtained by farmers increase the level of farmer participation in the UPSUS corn program. Farmer characteristics have a positive impact but do not possess a significant effect on the level of farmer participation.